Kamisama kiss. Vol. 17 - Suzuki, Julietta (Shojo beat manga., 2015)
Nanami has finally found the fallen kami who cursed Tomoe, but before she can rush home to save her beloved shinshi, she must watch the past unfold. But how will her relationship with Tomoe be affected by her standing witness to the torments he and Yukiji suffer?!